Salmonella Paratyphi A causing Endocarditis: A rare encounter - Bal, Harshvir; Chawla , Aadya; Shetty, Aakanksha; Sinan, Mohammad; Achappa, Basavaprabhu (Bangladesh Journal of Infectious Diseases, 2025)
With the trends of emerging paratyphi infections, especially in South Asia, the increase in the incidence of its rarer manifestations is around the corner. Here, we describe the case of Paratyphoid Endocarditis in a 55-year-old man, presenting to the ER with fever, vomiting, and aortic murmur, the subsequent diagnostic workup, and the treatment plan. The rarity of the disease has led to a scarcity of knowledge about the appropriate course of treatment, particularly whether surgery is required. Furthermore, a broader community-level strategy, such as the development of vaccines including the paratyphi strains, and measures to disrupt the modalities of disease transmission are required to curb the morbidity and mortality of Salmonella paratyphi. Bangladesh Journal of Infectious Diseases, December 2024;11(2):214-216